Nasal polyposis in Peutz–Jeghers syndrome: a distinct histopathological and molecular genetic entity. Issue 4 (14th June 2006) - de Leng, Wendy W J; Westerman, Anne Marie; Weterman, Marian A J; Jansen, Marnix; van Dekken, Herman; Giardiello, Francis M; de Rooij, Felix W M; Paul Wilson, J H; Offerhaus, G Johan A; Keller, Josbert J
Abstract : Background: Peutz–Jeghers syndrome (PJS) is an autosomal dominant hamartomatous polyposis syndrome of the gastrointestinal tract, caused by a germline STK11/LKB1 mutation. Nasal polyposis was described in the original report by Peutz. Recently, a molecular–genetic association between nasal polyposis and PJS has been reported. Objective: To further explore the occurrence and pathogenesis of PJS-related nasal polyposis. Methods: 51 patients with PJS, 84 unaffected family members and 36 spouses from 18 families with PJS were questioned for the presence of nasal polyposis. 12 PJS-related nasal polyps, 1 carcinoma of the nasal cavity and 28 sporadic nasal polyps were analysed for loss of (wild type) STK11/LKB1, eosinophilia, squamous metaplasia, dysplasia and expression of cyclo-oxygenase 2 and p53. Results: Nasal polyps occurred in 8 of 51 patients with PJS, and were not reported by non-affected family members (p<0.001). Germline STK11/LKB1 mutations were identified in all patients with PJS and nasal polyposis. Loss of heterozygosity was found in four of eight PJS-related nasal polyps, but not in sporadic nasal polyps (p = 0.002). PJS-related nasal polyps showed less eosinophilia than sporadic nasal polyps (p<0.001). Expression of cyclo-oxygenase 2 was found in 11 of 12 PJS-related nasal polyps and 19 of 28 sporadic nasal polyps (p>0.05). Overexpression of p53 was not found. Conclusions: Nasal polyposis occurs in a significant number of Dutch patients with PJS, one of whom developed a carcinoma in the nasal cavity. The loss of heterozygosity, and the absence of eosinophilia suggest a distinct pathogenesis compared with sporadic nasal polyposis.